(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article highlights the skills of mentally retarded students in mastering mathematical knowledge, the peculiarities of shaping geometric skills ,difficulties in studying geometric matirials, methods of teaching the teacher geometric shapes.